The contribution of love, and hate, to organizational ethics - Schwartz, Michael (College teacher); Harris, Howard (Head of Management Research); Comer, Debra R., 1960- (Research in ethical issues in organizations ;, 2016)
Ideally suited to researchers, postgraduates and professionals interested in key issues such as tax avoidance and corporate privacy, the latest volume of Research in Ethical Issues in Organizations examines how profit seeking and not for profit organizations can be conceived and designed to satisfy legitimate human needs in an ethical and meaningful way. The volume addresses a range of contemporary issues in applied and professional ethics and explores the unique role of organizational ethics in creating and sustaining a pluralistic, free enterprise economy.